The Effect Of Customer Experience And Risk Perception On Repurchase Intention Of Boba Drinks Mediated By Customer Satisfaction (Study On Mixue Denpasar Area) - Kyana, Ni Luh Gede Sari Marta; Wardana, I Made (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
One place that has been impacted by the phenomena of Mixue's rising popularity in Indonesia is Denpasar City, Bali. By 2023, Denpasar will already have fifty-eight percent of Bali's outlets. Conversely, Mixue's income is more likely to decrease. This study aims to investigate the role that satisfaction plays as a mediator between Mixue consumers' tendency to repurchase in Denpasar and their sense of experience and danger. This research is classified as associative quantitative research. The group under research consisted of consumers of Boba Mixue drinks in Denpasar City. The sample size was 158 respondents overall, and the method used was purposeful sampling. Data collection and surveying were done using a study instrument that resembled a questionnaire. In this work, the analytical approach used was PLS-based SEM analysis. The results showed that every variable had a significant effect. In the Denpasar region, satisfaction has a somewhat moderating role in resolving the impact of customer experience and risk perception on the desire to buy Boba Mixue beverages.